2008
DOI: 10.1080/02652030802136188
|View full text |Cite
|
Sign up to set email alerts
|

Fate ofFusariummycotoxins in maize flour and grits during extrusion cooking

Abstract: Extrusion technology is used widely in the manufacture of a range of breakfast cereals and snacks for human consumption and animal feeds. To minimise consumer exposure to mycotoxins, the levels of deoxynivalenol (DON) and zearalenone (ZON) in cereals/cereal products and fumonisins B(1) and B(2) (FB(1) and FB(2)) in maize are controlled by European Union legislation. Relatively few studies, however, have examined the loss of Fusarium mycotoxins during processing. The behaviour of FB(1), FB(2) and fumonisin B(3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
3
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 18 publications
1
35
3
1
Order By: Relevance
“…It is reasonable that soaking and heating with sodium bisulphite may reduce the concentration of DON in fried maize. On contrary to the studies mentioned above, Scudamore, Guy, Kelleher, and Macdonald (2008) observed that DON is more stable among other Fusarium toxins during extrusion cooking of maize. Therefore, a further study is necessary to reveal the influences of processing steps in fried maize.…”
Section: Analysis and Occurrence Of Deoxynivalenol In Samplescontrasting
confidence: 90%
“…It is reasonable that soaking and heating with sodium bisulphite may reduce the concentration of DON in fried maize. On contrary to the studies mentioned above, Scudamore, Guy, Kelleher, and Macdonald (2008) observed that DON is more stable among other Fusarium toxins during extrusion cooking of maize. Therefore, a further study is necessary to reveal the influences of processing steps in fried maize.…”
Section: Analysis and Occurrence Of Deoxynivalenol In Samplescontrasting
confidence: 90%
“…Conditions used during the extrusion process that may affect fumonisin reduction are summarized in Table 1. The moisture content and temperature are regarded as the main factors affecting expansion ratio while other factors including protein content may play an important role (Bhattacharya and others 1986; Scudamore and others 2008). The variations in expansion ratio may be attributed to relative protein contents since the moisture content and temperature of samples were kept constant.…”
Section: Resultsmentioning
confidence: 99%
“…The improved efficacy of twin‐ in contrast to single‐screw extrusion in reducing fumonisin levels may be a result of more complete mixing of sample in the barrel of a twin‐screw extruder (Connelly and Kokini 2007). Other studies have demonstrated that the stability of fumonisins during extrusion is influenced by several factors, including the screw configuration, screw speed, extrusion temperature, and moisture content of the food matrix (Katta and others 1999; Scudmore and others 2008). …”
Section: Resultsmentioning
confidence: 99%
“…Depending on the extrusion parameters (temperature, moisture content, screw speed) the zearalenone concentration was reduced by 66-83 % (Ryu et al, 1999), 66-81 % (Cetin and Bullerman, 2005) and 6-54 % (Scudamore et al, 2008a). Extrusion cooking of wheat spiked with 305 µg/kg of zearalenone resulted in a reduction rate of 3-17 % depending on the parameters used (Scudamore et al, 2008b). The addition of salt resulted in higher zearalenone levels indicating a lower reduction rate (Scudamore et al, 2008a).…”
Section: Milling and Food Processingmentioning
confidence: 99%